ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL OPERASI ALJABAR - Kanduli, Petrus Pati; Prayitno, Anton; Khasanah, Fitria (FKIP Universitas Wisnuwardhana, 2018)
This study aims to describe the mistakes made by 7th-grade junior high school students in worked on operational problems and to find out the factors that caused the error. The method used in this study was descriptive qualitative with a research subject of 5 students. The instruments of data collection are written tests and interviews. Five students were asked to solve the algebraic surgery problem and conduct interviews with subjects who had many errors. The results showed that there were two types of errors in working on algebraic operating problems, namely errors in putting concepts and errors in completing. Mistakes in putting the concept that is an error understanding the concept of algebra. The causes of errors in understanding the algebraic concept are indicated by lack of mastery of the material and lack of accuracy of students in the process of completion. While mistakes made by students are errors in doing calculations. Factors that cause errors in calculating when setting a time that is not following how to solve a problem that makes students become rushed and panic in writing answers; as a result, students cannot check the results of their work.Keywords: error analysis, mis-understand concept, problem solving error, algebraic operation